William Blake and the Daughters of Albion - Bruder, H. author. aut Link
XI, 291 p.
Keywords: William Blake and the Daughters of Albion offers a challenge to the Blake establishment. By placing some of Blake's early prophetic works in startingly new historical contexts (most provocatively those of female conduct and pornography) a very different image of the radical Blake emerges. The book shows what can be achieved when a challenging methodology, feminist historicism, is brought to bear on a canonical writer and on now canonized interpretations of his work.